Stimulus Driven Single Unit Activity From Micro-Electrocorticography - Hermiz, John; Hossain, Lorraine; Arneodo, Ezequiel M.; Ganji, Mehran; Rogers, Nicholas; Vahidi, Nasim; Halgren, Eric; Gentner, Timothy Q.; Dayeh, Shadi A.; Gilja, Vikash (Frontiers in Neuroscience, 2020)
High-fidelity measurements of neural activity can enable advancements in our understanding of the neural basis of complex behaviors such as speech, audition, and language, and are critical for developing neural prostheses that address impairments to these abilities due to disease or injury. We develop a novel high resolution, thin-film micro-electrocorticography (micro-ECoG) array that enables high-fidelity surface measurements of neural activity from songbirds, a well-established animal model for studying speech behavior. With this device, we provide the first demonstration of sensory-evoked modulation of surface-recorded single unit responses. We establish that single unit activity is consistently sensed from micro-ECoG electrodes over the surface of sensorimotor nucleus HVC (used as a proper name) in anesthetized European starlings, and validate responses with correlated firing in single units recorded simultaneously at surface and depth. The results establish a platform for high-fidelity recording from the surface of subcortical structures that will accelerate neurophysiological studies, and development of novel electrode arrays and neural prostheses.